Estimation of mechanical properties in Eucalyptus woods towards physical and anatomical parameters - Marini, Lucas José; Cavalheiro, Raquel Schmitt; Araujo, Victor Almeida de [UNESP]; Cortez-Barbosa, Juliana [UNESP]; Campos, Cristiane Inácio de [UNESP]; Molina, Júlio César [UNESP]; Silva, Diogo Aparecido Lopes; Lahr, Francisco Antonio Rocco; Christoforo, André Luis (Elsevier, 2022)
There is a perceptible opportunity to utilize eucalypts in value-added wooden products with structural features for construction. But, tests to determine the wood properties require specific equipment and technical training. As alternative, the study utilized optical microscopy to measure some anatomical elements of 10 eucalypt varieties to estimate their mechanical properties in line with anatomical parameters and bulk densities using regression models. Eight anatomical properties about constituent sizes and six mechanical properties about compression behaviors were evaluated. Regression models were positively conclusive, as R2 values were 94.15, 92.95 and 77.77 for the modulus of elasticity in compression parallel, compression parallel strength and shear stress parallel to the grain, respectively.
Keywords: Bulk density; Eucalyptus; Mechanical properties; Regression model; Wood anatomy